Photoelectrochemical Poperties of Anodic TiO2 Nanosponge Layers - Sanchez-Tovar, Rita; Lee, Kiyoung; Garcia-Anton, Jose; Schmuki, Patrik (ECS Electrochemistry Letters, 2013)
In the present work we grow TiO2 nanosponge structures by anodizing Ti in a glycerol/water/NH4F electrolyte to thickness of some extgreekmm. We evaluate the photoelectrochemical behavior (bandgap, photocurrent-voltage characteristics) in presence and absence of methanol. Methanol drastically affects the photoresponse (due to hole capture and current doubling). The optimum thickness for photoelectrochemical applications of these nanostructures is dependent on the excitation wavelength. For applications such as solar light water splitting, anodic sponge structure of ≈500 nm thickness can be beneficially used to increase the photoresponse compared to compact TiO2 layers.
EAM Import::2019-03-12